(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
This research seeks to analyze, within the historical context of the late nineteenth and early twentieth centuries, the contrasting portrayal of fashion in the posters of the prolific artist Alphonse Mucha compared to the predominant clothing styles of that period, which experienced the artistic and sophisticated atmosphere of Art Nouveau. The aim of this research is to study the historical context and aesthetic references of the Art Nouveau movement, analyzing women’s fashion during the Belle Époque, from the point of view of the socio-cultural transformations of this period, linked to the influence of Alphonse Mucha, as well as his influence on the Art Nouveau movement and fashion, investigating the nuances of the female figure in his works, understanding the influence of the colors of the Belle Époque on his creations and analyzing the portrayal and symbolism of fashion in his commercial posters. To this end, the methods used included screening the materials, content analysis, interpretation of the data collected, visual analysis of illustrations and photographs, description of Belle Époque clothing and its representations in the works of Alphonse Mucha, qualifying the study as bibliographical research of an exploratory nature. In addition, theoretical bases from scholars of the Belle Époque and the Art Nouveau movement and fashion historians were researched and analyzed. Therefore, the representation of fashion in Alphonse Mucha’s posters presents symbols and signs of a social change inherent to human evolution and the role of women as individuals with desires and belonging.